KV–kV and kV–MV DECT based estimation of proton stopping power ratio – a simulation study. (September 2021) - Li, Kai-Wen; Fujiwara, Daiyu; Haga, Akihiro; Liu, Huisheng; Geng, Li-Sheng
Highlights: A simulation-based method was proposed to predict stopping power ratio (SPR). The practical error in SPR was evaluated using an ICRP110 human phantom. kV-MV dual-energy CT can provide more accurate predictions than kV-kV dual-energy CT. Abstract: Purpose: This study aims to estimate the proton stopping power ratio (SPR) by using 80–120 kV and 120 kV–6 MV dual-energy CT (DECT) in a fully simulation-based approach for proton therapy dose calculations. Methods: Based on a virtual CT system, a two-step approach is applied to obtain the reference attenuation coefficient for image reconstruction. The effective atomic number (EAN) and electron density ratio (EDR) are estimated from two CT scans. The SPR is estimated using a calibration based on known materials to obtain a piecewise linear relationship between the EAN and the logarithm of the mean excitation energy, ln I m . The calibration phantoms are constructed from reference tissue materials taken from ICRU Report 44. Our approach is evaluated through using the ICRP110 human phantom. The respective influences of noise and beam hardening effects are studied. Results: With the beam hardening correction applied, the results of 120 kV–6 MV DECT are comparable to those of 80–120 kV DECT in predicting the EAN, but the former demonstrated a clear improvement in predicting the EDR and SPR. The 120 kV–6 MV DECT is able to predict the SPR within an accuracy of 10% for lung tissue and 5% for pelvis tissue, thereby outperforming the 80–120 kV DECT. Conclusions: The 120 kV–6 MV DECT is less sensitive to noise but more susceptible to beam hardening effects. By applying beam hardening correction, the 120 kV–6 MV DECT can predict the SPR more accurately than the 80–120 kV DECT. To utilize our DECT approach most effectively, high-quality reconstructed images are required.